Development of hybrid assembled composites with sensory function. Issue 1 (2015) - Kräusel, Verena; Graf, Alexander; Heinrich, Michael; Decker, Ricardo; Caspar, Mirko; Kroll, Lothar; Hardt, Wolfram; Göschel, Angela
Abstract: The assembly of piezoelements with sheet metals enables direct functional integration into formed sheet parts. Joining a thermoplastic polymer highly enriched with piezoceramic powder with thin metal sheets opens up new application areas. The re-meltable matrix of the composite is multi formable with a high degree of freedom. The properties, mainly the bonding strength, were investigated in processing separate samples. The analysis of the signal quality showed a good correlation between flat and formed hybrid assembled composites (HAC). However, the properties of the HAC and the signal amplitudes depend on compound formulation and surface roughness of the sheet metal.